If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1 = 19 Reorder the terms: -1 + 3z = 19 Solving -1 + 3z = 19 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3z = 19 + 1 Combine like terms: -1 + 1 = 0 0 + 3z = 19 + 1 3z = 19 + 1 Combine like terms: 19 + 1 = 20 3z = 20 Divide each side by '3'. z = 6.666666667 Simplifying z = 6.666666667
| x=3y+5y | | 56=x^2 | | 7y^2-20y+1=0 | | 15-x+2=-8 | | 12y-3=-7y+5 | | -.9x+9.65=-0.4x+8.65 | | 3b-13+4b=-9 | | -15=4x | | 2*2*2*2*2*2*2*2= | | 3x+4=6+x | | -66-6X=10X+24 | | 6w(-3)=(-4)-w | | 3+c+2c=-c(-1+5) | | 12x-18=24 | | -20=-5z | | 6-3n=5n-10n+18 | | 2(3y+6+3)=196-16 | | 24=6x-4y | | s^2-11s+30=0 | | 5(2x-14)+23=7x-14 | | 10a(2-7a)= | | x(6)+y(4)=24 | | 3(y-4)-5=-2 | | 7(2+5)=x | | x(6)+y(y)=24 | | n-2+n+2=0 | | 4(y+3)=48 | | 3x+2(x-9)=8x+x-14 | | -10-3x=-10 | | 80(x-8)=48(x+8) | | 4=h+2 | | 6=5p-5-4p |